2008
DOI: 10.5688/aj7205110
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student and Preceptor Perceptions of Preceptor Teaching Behaviors

Abstract: Objectives. To compare PharmD students' and preceptors' perceptions of preceptors' teaching behaviors. Methods. A 47-item survey instrument was developed and distributed to students and preceptors for rating the frequency and adequacy of each teaching behavior as not done, done but inadequate, and well done and adequate. Results. Seventy-seven (99%) students and 53 (55%) preceptors responded to the survey. Students were somewhat satisfied with their preceptors' teaching behaviors. In comparison, preceptors ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 12 publications
4
55
2
Order By: Relevance
“…1 To achieve this goal, Preceptors play crucial roles in pharmacy practice experience, as a teacher, mentor, and evaluator by showing students how to apply knowledge gained in their didactic courses to actual clinical practice, by helping students engage in pharmacy activities, and by assessing their performance and providing effective feedback. 2,3 Thus, the recruitment and retention of qualified preceptors is essential to a successful experiential education system.…”
Section: Introductionmentioning
confidence: 99%
“…1 To achieve this goal, Preceptors play crucial roles in pharmacy practice experience, as a teacher, mentor, and evaluator by showing students how to apply knowledge gained in their didactic courses to actual clinical practice, by helping students engage in pharmacy activities, and by assessing their performance and providing effective feedback. 2,3 Thus, the recruitment and retention of qualified preceptors is essential to a successful experiential education system.…”
Section: Introductionmentioning
confidence: 99%
“…3 Compared with feedback from student evaluations, preceptors overestimate their own performance, particularly in the areas of providing adequate student feedback and evaluation, suggesting a critical need for preceptor development programs. 4 In 2008, the American Pharmacists Association called for more standardization in the quality of experiential education and has identified preceptor training as a component of this standardization. 5 Quality of preceptor training influences the quality of experiential education.…”
Section: Introductionmentioning
confidence: 99%
“…11 As one study showed, pharmacy preceptors had a tendency to overestimate their skills related to teaching compared to student perceptions of their actual performance. 12 Likewise, these scores are based on preceptor perceptions and do not depict their actual level and quality of performance. The self-evaluation is not a validated measure of their competency.…”
Section: Discussionmentioning
confidence: 99%